Windows into men's souls : religious nonconformity in Tudor and early Stuart England - Campbell, Kenneth L. (Lexington Books, 2012)
Windows into Men's Souls focuses on the ways in which the concept of religious nonconformity was inherent in the English Reformation. The book's uniqueness lies in its blending of different historiographical traditions dealing with Puritans, Catholics, and Separatists while melding them into a coherent and interpretive analysis of the phenomenon of religious nonconformity as a whole and the religious and intellectual impulses behind it.